Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menerapkan Metode MAUT - Muhammad Annur Al Fajar Nst; M. Hasyim Arrasyid; Eferoni Ndruru (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The selection of the best employee is the company's appreciation for the performance of its employees. This can motivate employees to be more motivated at work. To get the names of the best employees, a system is needed that performs the expected selection process and can produce objective and transparent information. In finding the best employees, the company does this by appointing without a reliable enough assessment. Therefore, a decision support system is needed in evaluating employee performance. This research uses the multi-attribute utility theory method. The data processed for this evaluation are 10 samples from CV Aurelia Weida Prima Medan. The evaluation is based on several criteria and weights given. There are 6 data criteria to assess employee performance, namely service (30% weight), integrity (20% weight), commitment (15% weight), discipline (20% weight), cooperation (13% weight), and employee performance (12% weight). From the calculation results, the employee who has the highest score is obtained. Therefore, the maximum value is obtained at A9 = 15.746, and the minimum value is obtained at A1 = 1.410. Will be considered for CV later. Aurelia Weida Prima Medan evaluates its employees over a while. It turns out that choosing the best employee performance helps CV. Aurelia Weida Prima Medan